APPLICATION OF A PROCESS MODEL FOR THE MANAGEMENT OF INTELLECTUAL PROPERTY IN A TECHNOLOGY LICENSING OFFICE FROM A BRAZILIAN RESEARCH CENTER - Andrade, Herlandi de Souza [UNESP]; Chagas, Milton de Freitas; Soto Urbina, Ligia Maria; Silva, Messias Borges [UNESP] (Univ Nove Julho, 2017)
In Brazil, the Technology Licensing Office (TLO) are responsible for managing the innovation policy of Scientific and Technological Institutions (STI). However, when analyzing the functioning of the TLO is possible to observe that these are organizations that still require capacitation to perform with efficiency and efficacy of its functions. Thus, the aim of this paper is to report the application of a model for the management of Intellectual Property (IP) in the TLO of the Instituto Nacional de Pesquisas Espaciais (INPE-TLO), in Brazil, which was conducted through an action research. The application of such a model is intended to empower INPE-TLO to perform its functions relating to the protection and commercialization of technologies in order to promote the transfer of technologies created by research and development units of the INPE to the productive sector. As preliminary results, it is possible to highlight the development of an action plan to realignment the flow of activities as well as to customize the model proposed to culture and INPE-TLO structure.
Keywords: Technological Innovation; Intellectual Property; Technology Protection; Technology Commercialization; Technology Transfer